Dla kogo pracuje dziś Król Artur? Użycia i nadużycia mitu arturiańskiego - ROJEK, PATRYCJA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Who does King Arthur work for today? Uses and abuses of the Arthurian myth Analyzing the phenomenon of one of the most popular European myths - the Arthurian myth - the author attempts to answer the question of the difference between using and abusing myths. An insight into the sources of Arthurian tradition proves that even the oldest and most important literary incar- nations of the myth were used by their authors as a means of speaking about contemporary political and sociological issues. However, the Arthurian films (which are the main subject of this research) reinforce the thesis about a distinctive feature of a myth itself to be immensely flexible and able to absorb various cultural content. The study examines in detail the film King Arthur (2004, dir. Antoine Fuqua). Its creators seem to come very close to the border between use and abuse of a myth by denying the mythical aspect of the Arthurian legends